A multicenter retrospective evaluation of the prevalence of known and presumed hereditary eye diseases in Lagotto Romagnolo dog breed within a referral population in Italy (2012–2020). (17th August 2022) - Crasta, Manuela; Arteaga, Kevin; Barachetti, Laura; Guandalini, Adolfo
Abstract: Objective: To describe the ophthalmological findings of Lagotto Romagnolo dog breed and to report the prevalence of Known and Presumed Hereditary Eye Diseases (KP‐HED). Animals Studied: Two hundred sixteen dogs were examined and included in this retrospective study. Procedures: Medical records of Lagotto Romagnolo dogs between 2012 and 2020 were included. Data about the ocular status were collected through ocular screening examinations (OSE) or clinical ophthalmic examinations (COE). The prevalence of each KP‐HED was expressed as a function of the total number of the KP‐HED in this referral population. Results: A total of 85 dogs (39.35%) were ophthalmologically healthy, ocular diseases presumably not hereditary were found in 43 dogs (19.91%), and 88 dogs (40.74%) were affected by one KP‐HED. The most common KP‐HEDs diagnosed were cataract (28/88; 31.82%), corneal endothelial dystrophy (17/88; 19.32%), retinal dysplasia (9/88; 10.23%), lens instability (7/88; 7.95%), progressive retinal atrophy (6/88, 6.82%), and keratoconjunctivitis sicca (6/88, 6.82%). Most of dogs with a KP‐HED (77.27%, 68/88) were identified within COE group. Conclusions: To the authors' knowledge, this is the first report of the prevalence of ocular disease in the Lagotto Romagnolo dog breed within a referral population in Italy. This study suggests a relatively high prevalence of KP‐HED, with a characteristic late‐onset presentation in some diseases. Many of these KP‐HED's, lead to ocular pain and irreversible blindness, for this reason, the authors highlight the importance of aiming for an early diagnosis. Breeder's efforts and breeding programs should be directed at limiting such disorders.